Access To Justice In Plural Legal Systems: A Case Study Of Customary And State Law Integration In Sub-Saharan Africa - Lindie Mokgadi (Journal of Law, Policy and Global Development, 2025)
This study explores access to justice in plural legal systems by examining the integration of customary law and state law in Sub-Saharan Africa. In many African states, legal pluralism is a historical and social reality, with indigenous customary practices coexisting alongside colonial-derived formal legal frameworks. While state law often claims supremacy, customary law remains the primary source of dispute resolution for a significant proportion of the population, especially in rural areas. This case study investigates how the interaction between these two systems affects legal accessibility, fairness, and legitimacy. Through a qualitative case study methodology involving document analysis and secondary data, the research highlights both the complementarities and tensions between the two legal regimes. The findings suggest that harmonizing customary and state law—through mutual recognition, procedural safeguards, and institutional cooperation—can enhance inclusive justice outcomes. However, unresolved issues related to gender equality, due process, and jurisdictional ambiguity persist. The study concludes that plural legal systems, when effectively integrated, offer a promising pathway to justice that is both contextually relevant and socially legitimate